2011
DOI: 10.1007/s11999-010-1488-0
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii is not Associated with Osteomyelitis in a Rat Model: A Pilot Study

Abstract: Background Multidrug resistant Acinetobacter baumannii (MDR AB) with and without Staphylococcus aureus (SA) is a commonly isolated organism in infected segmental bone defects in combat-related trauma in Iraq and Afghanistan. Although MDR AB in visceral infections is a therapeutic challenge, control of infection appears more common for combat-related osteomyelitis.Questions/purposes Using a rat model, we explored the virulence of MDR AB in segmental bone defects alone and in combination with SA. Methods Segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…Conversely, A baumannii was not present in any 12-week cultures, but rather other antibiotic-resistant ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, K pneumoniae, A baumanii, P aeruginosa, and Enterobacter species) such as enteric organisms Enterococcus faecium and Enterobacter cloacae as well as various Gram-positive staphylococci, but not S aureus were isolated at time of culture (Table 1). Negative culture results for A baumannii infection 12 weeks postinoculation are consistent with previous rat studies and may be the result of decreased virulence in bone as compared with other infection sites [9]. Secondary infection with other nosocomial pathogens, particularly Gram-positive organisms, is consistent with clinical findings and suggests that initial infection with A baumannii may produce an environment conducive to secondary infection or overgrowth of other nosocomial organisms [17].…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, A baumannii was not present in any 12-week cultures, but rather other antibiotic-resistant ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, K pneumoniae, A baumanii, P aeruginosa, and Enterobacter species) such as enteric organisms Enterococcus faecium and Enterobacter cloacae as well as various Gram-positive staphylococci, but not S aureus were isolated at time of culture (Table 1). Negative culture results for A baumannii infection 12 weeks postinoculation are consistent with previous rat studies and may be the result of decreased virulence in bone as compared with other infection sites [9]. Secondary infection with other nosocomial pathogens, particularly Gram-positive organisms, is consistent with clinical findings and suggests that initial infection with A baumannii may produce an environment conducive to secondary infection or overgrowth of other nosocomial organisms [17].…”
Section: Discussionsupporting
confidence: 85%
“…A recent pilot study using a rat model suggested that MDR A. baumannii did not appear to cause or contribute to osteomyelitis [15]. However, in our patient, isolation of A. baumannii from several bone specimens, including the ones collected intraoperatively, implies a significant role.…”
Section: Discussioncontrasting
confidence: 46%
“…In the experimental rat model, inoculation of S. aureus and A. baumannii was associated with osteolysis, whereas A. baumannii alone lead to osteoblastic activity [15]. The initial bone culture in our patient failed to show S. aureus; however the intraoperative culture grew both S. aureus and A. baumannii.…”
Section: Discussionmentioning
confidence: 61%
“…The mammalian models and end-points have varied in complexity and strength, and have included a mouse or rat pneumonia model, as well as a rat soft-tissue model where bacteria are injected into a soft-tissue pouch and then the pouch is sampled over time for bacterial density. A pilot study assessing A. baumannii infection of bone in a rat model has also been performed (45). Virulence factors that have been identified using this approach include penicillinbinding protein 7/8 (20), a glycosyltransferase (LpsB) involved in LPS biosynthesis (23), and genes (ptk and epsA) important for capsule formation (22).…”
Section: Use Of In Vivo Mammalian Model Systems To Study a Baumanniimentioning
confidence: 99%